2015
DOI: 10.1016/j.anorl.2013.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of a case of adult epiglottic laryngomalacia

Abstract: Excessive resection of the epiglottis may lead to false passage; insufficient resection risks being ineffective. V-shaped partial epiglottectomy minimizes risk of false passage while ensuring permanent respiratory airflow via the epiglottic V during epiglottic movement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
1
7
0
1
Order By: Relevance
“…The importance of active glottal closure in prevention of aspiration is further supported by the well‐recognized risk of aspiration in dogs with laryngeal paralysis despite a normally functioning epiglottis . The human literature is mixed regarding the risk of aspiration after epiglottectomy . Abscessation of I‐EP occurred in 1 dog in our study after initial failed hyoepiglotticus imbrication and has not been reported as a complication in previous studies.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The importance of active glottal closure in prevention of aspiration is further supported by the well‐recognized risk of aspiration in dogs with laryngeal paralysis despite a normally functioning epiglottis . The human literature is mixed regarding the risk of aspiration after epiglottectomy . Abscessation of I‐EP occurred in 1 dog in our study after initial failed hyoepiglotticus imbrication and has not been reported as a complication in previous studies.…”
Section: Discussionsupporting
confidence: 58%
“…7 The human literature is mixed regarding the risk of aspiration after epiglottectomy. [8][9][10][11][12][13][14] Abscessation of I-EP occurred in 1 dog in our study after initial failed hyoepiglotticus imbrication and has not been reported as a complication in previous studies.…”
Section: Discussionmentioning
confidence: 87%
“…It is difficult to properly determine the volume of epiglottis to cut without causing postoperative sequelae. Bartolomeo et al [32] described their experiences with a 25-year-old man with laryngomalacia managed using CO2 laser V-shape partial epiglottectomy. The authors stated that this treatment minimizes the risk of false passage, while ensuring permanent respiratory airflow through the epiglottic V during epiglottic movement.…”
Section: Partial Epiglottectomymentioning
confidence: 99%
“…Epiglotektomi parsial. 22 Whymark 6 melakukan epiglottopeksi pada 73% dari 58 bayi dengan LM derajat berat dimana didapatkan perbaikan stridor dan peningkatan berat badan pasien pasca operasi. Dilakukan ablasi mukosa lingual epiglotis dan mukosa pangkal lidah menggunakan laser CO2, kemudian epiglotis dan pangkal lidah dijahit menggunakan benang absorbable (gambar 9).…”
Section: Gambarunclassified